Evaluation of the potential of commercial use of microalgae in the world and in Ukraine. Issue 3 (1st December 2020) - Pavliukh, Lesia; Shamanskyi, Sergii; Boichenko, Sergii; Jaworski, Artur
Abstract : Purpose: This paper aims to evaluate of the microalgae potential for commercial application, in particular to conduct experimental study of biogenic compounds removal from sewage waters by microalgae, and to calculate economical benefits from biofertizers and biofuel production. Design/methodology/approach: Experimental study in the concentration change of nitrogen and phosphorus compounds in the cultivation of Chlorella Vulgaris microalgae in various types of sewage water was carried out. Findings: The efficiency wastewater treatment by microalgae was confirmed. The economic benefit from the biomass utilization as biofuel production was calculated. Practical implications: Implementation of wastewater treatment technology with biomass recycling for biofuel and biofertilizers production will minimize the impact on the environment. Originality/value: As a results of experimental studies, the ability of microalgae to reduce biogenic elements in wastewater was confirmed. Microalgae can be used both for wastewater treatment to biogenic elements removal, such as phosphorous and nitrogen compounds, and biofuel, biofertilizers production. Prospects of the commercial use of microalgae are obvious. They are specially adapted to an environment dominated by viscous forces.